?MIXED MONO TONICITY THEOREMS FOR A SYSTEM OF ABSTRACT MEASURE DELAY INTEGRO-DIFFERENTIAL EQUATIONS (Biological Sciences - PJSIR, 1999)
In this paper the existence of extremal solutions of a system of nonlinear abstract measure delay integra-differential equations is established using the fixed point theorem of Tar ski. Two basic integra-differential inequalities are obtained which are further applied to prove the boundedness and uniqueness of the solution of related abstract measure delay integra-differential equations.